Analysis of the impact of different landing heights and lateralities on lower limb joint load based on statistical parametric mapping - Lian Duan; Yuan Gao; Feng Gao; Yang Sun; Naiyuan Tian (PLoS ONE, 2025)
This study aimed to investigate the effects of landing height and limb laterality on lower limb joint loading using Statistical Parametric Mapping (SPM), thereby providing insights for injury prevention and optimizing performance in dynamic sports. Twenty male participants were assessed using the Qualisys 3D motion capture system and Kistler 3D force plates during landings from 30 cm and 45 cm on both dominant and non-dominant legs. No significant interaction effects between landing side and height were observed, but landing on the non-dominant leg increased the ankle joint internal rotation moment. The knee’s abduction moment significantly increased during the 17%−37% landing phase, and the hip’s abduction moment significantly increased during the 86%−100% phase. Higher landing height significantly increased vertical ground reaction force (GRF) during the mid-buffering phase (23%−35%). Landing on the dominant side was linked to an elevated risk of lower limb joint injuries due to increased abduction moments at the hip, external rotation moments at the knee, and internal rotation moments at the ankle. Furthermore, greater landing height correlated with higher vertical GRF, intensifying stress on the lower limbs and increasing injury risk. To reduce the risk of injury, training should focus on increasing strength and control of the non-dominant leg and controlling landing height.